2009
DOI: 10.1128/aem.01764-08
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation and Posttranslational Processing of the Class II Hydrophobin Genes from the Biocontrol FungusHypocrea atroviridis

Abstract: Hydrophobins are small extracellular proteins, unique to and ubiquitous in filamentous fungi, which mediate interactions between the fungus and environment. The mycoparasitic fungus Hypocrea atroviridis has recently been shown to possess 10 different class II hydrophobin genes, which is a much higher number than that of any other ascomycete investigated so far. In order to learn the potential advantage of this hydrophobin multiplicity for the fungus, we have investigated their expression patterns under differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Interestingly, none of the hydrophobin genes was expressed in 3-day-old mycelium in liquid culture, although HYD1 was seen in mycelium grown on solid medium. In Hypocrea atroviridis, diVerential expression patterns were dependent on diVerent physiological conditions for the ten diVerent class II hydrophobin genes, and there appeared to be both divergent and redundant patterns among HYD genes (Mikus et al 2009). Fang et al (2007) showed that a M. anisopliae G protein signaling (RGS) protein, cag8, aVects ssgA/HYD1 expression; transcript levels were markedly reduced in cag8 gene mutants and they also lost pigmentation in liquid culture.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, none of the hydrophobin genes was expressed in 3-day-old mycelium in liquid culture, although HYD1 was seen in mycelium grown on solid medium. In Hypocrea atroviridis, diVerential expression patterns were dependent on diVerent physiological conditions for the ten diVerent class II hydrophobin genes, and there appeared to be both divergent and redundant patterns among HYD genes (Mikus et al 2009). Fang et al (2007) showed that a M. anisopliae G protein signaling (RGS) protein, cag8, aVects ssgA/HYD1 expression; transcript levels were markedly reduced in cag8 gene mutants and they also lost pigmentation in liquid culture.…”
Section: Discussionmentioning
confidence: 97%
“…Of those, 60% were from the eukaryotic orthologous groups (KOGs) involved in the cell processes of post-translational modification (HSPs, aspartyl protease, serine protease, glutathione peroxidase, ATPase), and amino acid and lipid metabolism. The most abundantly expressed genes encoded the CPC1 transcription factor (7); a type II hydrophobin (85); a glyceraldehyde 3-phosphate dehydrogenase highly represented in EST collections of T. reesei (32), T. harzianum (140), and T. longibrachiatum (141); an enolase, also identified in the interaction proteome of T. harzianum (50), involved in thermal tolerance, glycerol synthesis, and salt stress. In addition, genes encoding aspartyl and subtilin-like serine proteases were found to be highly expressed in different EST collections of biocontrol strains (73,118,141), which supports the hypothesis of their involvement in the first stages of mycoparasitism (96,98,123).…”
Section: Expressed Sequence Tags (Ests)mentioning
confidence: 99%
“…Hydrophobins are small secreted proteins, found in the outer surface of the cell wall of hyphae and conidia. In this regard, hfb-2c, hfb-6a, and hfb-6b are expressed in T. atroviride under the conditions and time at which conidia are observed (1088). In T. reesei, expression of plant cell wall-degrading enzymes was found to be a major event during conidiation (352).…”
Section: Asexual Developmentmentioning
confidence: 99%
“…Recently, a novel subclass of hydrophobins was proposed for Trichoderma (27). The 10 T. atroviride hydrophobin genes are expressed in response to various conditions, including exposure to light pulses, starvation, and injury, but do not show mycoparasitism-specific regulation patterns (1088). Moreover, T. reesei hfb1 (TR_73173, TA_258206, and TV_60531) and hfb2 (TR_119989, TA_258295, and TV_91466) are regulated in response to light and by the G-protein alpha-subunit GNA1 (617).…”
Section: Hydrophobins and Cerato-platanin Proteinsmentioning
confidence: 99%